2018
DOI: 10.1016/j.enbuild.2018.06.030
|View full text |Cite
|
Sign up to set email alerts
|

A review on occupant behavior in urban building energy models

Abstract: Urban building energy models aspire to become key planning tools for the holistic optimization of buildings, urban design, and energy systems in neighborhoods and districts. The energy demand of buildings is largely influenced by the behavior of the occupants. The insufficient consideration of occupant behavior is one of the causes to the "performance gap" in buildings -the difference between the simulated and the actually observed energy consumption. On the urban-scale impacts of different occupant behavior m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(78 citation statements)
references
References 94 publications
0
75
0
3
Order By: Relevance
“…For a discussion on the potential biases introduced by considering only places with available data, we refer to the limitations in section 6. In this initial exploratory analysis, we are interested in the representative data-driven schedule of occupancy for each geographic location and use-type for direct comparison with the status-quo of occupancy modeling, which especially on the district-and urban-scale use ASHRAE standard schedules [23,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a discussion on the potential biases introduced by considering only places with available data, we refer to the limitations in section 6. In this initial exploratory analysis, we are interested in the representative data-driven schedule of occupancy for each geographic location and use-type for direct comparison with the status-quo of occupancy modeling, which especially on the district-and urban-scale use ASHRAE standard schedules [23,50].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our review of occupant behavior in urban building energy models [23], we found that standard schedules of occupancy are used in research beyond their original purpose. We found tools and studies that used standard schedules, among others, to:…”
Section: Origins and Purposes Of Standard Occupancy Schedulesmentioning
confidence: 99%
“…Unwanted infiltration, which has been studied as an external parameter affecting the energy loads of buildings, has been found to be an important factor in energy consumption reduction (Mattingly and Peters, 1977;Anderlind, 1985;Ren and Chen, 2015;Happle et al, 2018). In a recent study, Goubran et al (2017) calculated the infiltration rate in glass entrance doors through simulations and experiments.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Research on scalable residential end-use energy demand models for large scale building stocks is relatively new, if compared to the research developed to predict energy and thermal performance of individual buildings [3]. Most of the modelling techniques which have been developed to simulate the energy demand from small to large scale have been collected by several reviews [3][4][5][6][7][8][9]. In these papers, the modelling techniques are separated into two main categories: top-down and bottom-up.…”
Section: Introductionmentioning
confidence: 99%